Chemistry Learning Based on Kibas Asah Module (Wetland-Based Chemistry) Integrated AR-Sparkol on Buffer Solution Material: Students' Cognitive and Motivation Diagnostic - Almubarak Ali; Muhammad Fakhri Nawidi; Nurusshobah Nurusshobah; Santi Dwi Sadiah (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2019)
The learning process with a module based on local wisdom is the alternative way on how to make students' ability for analyzing and identifying be stronger, especially in learning chemistry and also their motivation. Chemistry learning does not only focus on material content but on how students can interpret content scientifically so that they have a broad and deep range of knowledge. This research was quantitative. It aimed to know the level of students' cognitive and motivation in learning chemistry where they were using a specific module. In this case, the kibas asah integrated Augmented Reality-Sparkol has been used. The research method used experimental research with the type of one-shot case study. The data collecting technique was a questionnaire, and it included a cognitive test and motivation. The data analyzing method was a descriptive statistics approach. The result showed that the level of students’ cognitive through two tests in a different location. Its value was in a row of 0,77 and 0,70 with “high” criteria, and students’ motivation value was 77,61 with strong criteria. These results showed that chemical learning based on the module was developed, and it can fix the quality of the students’ cognitive and motivation deeply. That is, the concept of research is not oriented towards the product produced, but how the product has implications for learning chemistry holistically, becoming a source of scientific reference, honing skills in using technology, creativity, critical thinking, mental models, habituating scientific attitudes, and increasing their knowledge both in terms of chemical content or environmental based references (local wisdom).